Export-led growth hypothesis new evidence from Thirlwall's idea - Choong, Chee-Keong; Yusop, Zulkornain; Law, Siong-Hook (The Philippine Review of Economics, 2007)
This study reexamines the relationship between exports and economic growth in ten East Asian and Pacific economies by building upon Verdoorn's [1941] idea. The cointegration tests indicate the existence of long-run and stable relationships between economic growth, exports, imports, capital, and labor in each economy. Granger-causality tests indicate short-run in causality (either export-led growth or growth-driven exports) in most economies. Besides, among the long-run estimated coefficients between exports and imports, Fiji, Hong Kong, Japan, Malaysia, and the Philippines satisfy the intertemporal budget constraints that is, these economies have an effective international trade policy to balance their trade position. The findings are in line with traditional trade theories and some recently developed endogenous growth theories.